AN ANALYSIS OF LIBRARY SERVICE QUALITY USING THE IMPORTANCE-PERFORMANCE ANALYSIS (IPA) METHOD - Rudamin, Rudamin; Kaharuddin, Kaharuddin; Mansyur, Mansyur (Universitas Labuhanbatu, 2025)
Purpose – This study aims to analyze the quality of library services at SMAN 9 Tana Toraja based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy.Methodology – This research employs a descriptive quantitative approach, utilizing the Importance-Performance Analysis (IPA) model. The study population consisted of 525 students who regularly use the library at SMAN 9 Tana Toraja, with a sample of 228 students determined using the Slovin formula. Data was collected through questionnaires distributed via Google Forms and analyzed using a Cartesian diagram to map performance against importance.Findings – The overall suitability level of library services was 83.086%, categorized as